Transmigration, The Indonesian Engineered Community: An Insight from Baras of West Sulawesi - Mukrimin, Mukrimin; Acciaioli, Greg (Komunitas, 2023)
This article is a study of transmigration in Sulawesi, Indonesia. Transmigration is the resettlement of transmigrants from a densely populated area to a less populated one. This article makes a valuable contribution to the field of literary studies by offering a contemporary analysis of transmigration in Indonesia, spanning from the Dutch colonial era to the present day. This article highlights that Indonesia is the most aggressive country in resettling about 7,936,6651 of its population to mainly the Outer Islands through transmigration programs from time to time. Among the settlement area which the focus of this study is the first documented Bugis state-sponsored migration in Baras of West Sulawesi. The transmigration in Baras was implemented by incorporating the so-called KTM (Kawasan Terpadu Mandiri - Self-Sufficient Integrated Area) and APPDT (Alokasi Penempatan Penduduk Transmigrasi - Special Allocation for Settled-Transmigration Area). The KTM then has turned into a frontier settlement, a frontier of agriculture, a frontier of an economy, and a frontier of politics. It is an open door for voluntary and involuntary transmigrants to access a resource.